2023
DOI: 10.1128/jvi.00437-23
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus BBLF1 Mediates Secretory Vesicle Transport to Facilitate Mature Virion Release

Abstract: Several viruses have been linked to the development of cancer in humans. Epstein-Barr virus (EBV), the first identified human oncovirus, causes a wide range of cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
0
0
0
Order By: Relevance
“…BBRF3 (gN/gM) [68] and the KSHV glycoprotein gB [83] contribute to viral assembly and egress. Another study, using a combination of electron microscopy and subcellular fractionation analyses, demonstrated that BBLF1 knockout leads to the accumulation of virions in secretory vesicles, suggesting its importance in EBV virion release [42]. A recent study demonstrated that BGLF4 induces cytoskeletal rearrangement, which is the coordinately induced redistribution of cytoplasmic organelles.…”
Section: Trafficking Of Matured Virions To the Plasma Membrane And Ex...mentioning
confidence: 99%
“…BBRF3 (gN/gM) [68] and the KSHV glycoprotein gB [83] contribute to viral assembly and egress. Another study, using a combination of electron microscopy and subcellular fractionation analyses, demonstrated that BBLF1 knockout leads to the accumulation of virions in secretory vesicles, suggesting its importance in EBV virion release [42]. A recent study demonstrated that BGLF4 induces cytoskeletal rearrangement, which is the coordinately induced redistribution of cytoplasmic organelles.…”
Section: Trafficking Of Matured Virions To the Plasma Membrane And Ex...mentioning
confidence: 99%
“…Additionally, this virus presents tegument proteins, whose functions are varied. They are associated with the release of mature virions, infectivity, viral production, and the inhibition of the host's antiviral response [172][173][174][175][176].…”
Section: Epstein-barr Virusmentioning
confidence: 99%